Mental health, physical self and lucid dreaming: A correlational study in sport students - Jones, Steven M R; Stumbrys, Tadas (International Journal of Dream Research, 2014)
It has been suggested that the ability of lucid dreaming is positively associated with both mental and physical health, which in turn seem to be also interrelated. The present study in a sample of sport science students (N = 72) investigated the relationships between lucid dream frequency, mental well-being and physical self-concept. Marsh’s Physical Self-Description Questionnaire (PSDQ) was used to measure physical self-concept as an indicator of physical fitness and two measures of mental well-being were employed, the Warwick Edinburgh Mental Well-Being Scale (WEMWBS) and Ryff’s Scale of Psychological Well-Being (RPWB). Lucid dreaming was found to be negatively associated with physical self-concept. Although mental well-being was not related to lucid dream frequency, it was strongly associated with physical self-concept. Future research should explore the relations in a less physically active and fit sample, and could benefit from including external physical measures.